Faktor – Faktor Penyebab Underpricing Saham Saat Initial Public Offering di BEI Periode 2016 – 2018 - Rizal Asrifin; Rachma Agustina (JFAS : Journal of Finance and Accounting Studies, 2021)
Initial Public Offering (IPO) is a company activity in order to sale its shares to public with the purpose to increasing company capital, and aimed to have an impact on company’s prospect improvement that occur due to expansion with those added capitals. Underpricing is a phenomenon where the price of shares offered in the primary market has a lower price then the price of shares in the secondary market. The aim of this study is to investigate whether there is an impact on auditor's reputation, underwriter's reputation, and Return on assets (ROA) on the underpricing of shares in companies performing IPO on the Indonesian Stock Exchange from 2016-2018. The result of this research shows that auditor's reputation, underwriter's reputation, and the return on assets has a significant impact on the underpricing level.